2017
DOI: 10.1248/bpb.b17-00143
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Oral Administration of Magnesium Ameliorates Dextran Sulfate Sodium-Induced Colitis in Mice through a Decrease of Colonic Accumulation of P2X7 Receptor-Expressing Mast Cells

Abstract: The number of patients with colitis has been increasing year by year. Recently, intestinal inflammation, as one of the factors for its onset, has been demonstrated to be induced by P2X7 receptor-mediated activation of colonic immune cells such as mast cells. Activation of P2X7 receptor (P2X7R) is known to be inhibited by divalent metal cations such as magnesium, but whether or not magnesium administration prevents/relieves colitis is unknown so far. Here, we report that oral (per os (p.o.)) administration of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
(65 reference statements)
2
19
0
Order By: Relevance
“… 24 Preventive oral magnesium could ameliorate colitis by reducing the accumulation of P2X7R-expressing mast cells in the colon. 40 In addition to intestinal inflammation, studies have shown that ATP-driven mast cell activation by P2X7R is also a potential trigger for neuro-inflammation and pain sensitization in migraine. 25 Until now, the relationship between P2X7R in mast cells and inflammatory pain has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Preventive oral magnesium could ameliorate colitis by reducing the accumulation of P2X7R-expressing mast cells in the colon. 40 In addition to intestinal inflammation, studies have shown that ATP-driven mast cell activation by P2X7R is also a potential trigger for neuro-inflammation and pain sensitization in migraine. 25 Until now, the relationship between P2X7R in mast cells and inflammatory pain has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, eATP/P2X7R-mediated activation of mast cells not only induces degranulation and inflammatory cytokines, but also chemokines and leukotriene B4 (LTB4) to recruit inflammatory cells (e.g., neutrophils) and subsequently exacerbate intestinal inflammation [18] (Figure 1). Therefore, targeting eATP-mediated mast-cell activation might be a promising novel strategy for the prevention and treatment of intestinal inflammation [70]. In another setting, eATP-P2X7R induced the death of regulatory T cells (Treg), which suppress colitis [63,71].…”
Section: Eatp As An Inflammatory Mediator In Intestinal Inflammationmentioning
confidence: 99%
“…In the GI system, P2X7R expressed in different cell types has various actions under homeostatic and pathological conditions studied under different experimental models, e.g., colitis model ( Gulbransen et al, 2012 ; Kurashima et al, 2012 ; Antonioli et al, 2014 ; Marques et al, 2014 ; Neves et al, 2014 ; Hofman et al, 2015 ; Wan et al, 2016 ; Figliuolo et al, 2017 ; Hashimoto-Hill et al, 2017 ; Ohbori et al, 2017 ; Diezmos et al, 2018 ; Souza et al, 2020 ; Saber et al, 2021 ), sepsis model via caecal ligation and puncture (CLP) ( Wu et al, 2017 ; Alarcón-Vila et al, 2020 ), infection models ( Keating et al, 2011 ; Huang et al, 2017 ; Shimokawa et al, 2017 ; Liu et al, 2018 ; Quan et al, 2018 ; Stark et al, 2018 ) in both animal and human studies. There were also a few studies ( Bourzac et al, 2013 ; Proietti et al, 2014 ; Arguin et al, 2017 ; Perruzza et al, 2017 ; Perruzza et al, 2019 ; Proietti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%